Long Term Outcome and Histologic Findings of a Retinal Astrocytic Hamartoma Treated with Intravitreal Injection of Anti-VEGF: A Case Report. (24th September 2021) - Ahmad, Kinza T.; Mansour, Hana A.; Rollins, Benjamin T.; Oviedo, Sergio Pina; Phillips, Paul H.; Uwaydat, Sami H.
Abstract : Background . To our knowledge, this is the first report to describe the histologic changes of a retinal astrocytic hamartoma (RAH) in a patient with tuberous sclerosis complex (TSC) treated with antivascular endothelial growth factor (anti-VEGF), as well as the longest anti-VEGF treatment that such a patient has received (3 years). Case Presentation . We present a case of a 20-year-old female with TSC who developed progressive growth of a papillary astrocytic hamartoma that caused significant retinal edema, vitreous hemorrhage, and neovascular glaucoma. The patient was initially treated with 25 intravitreal anti-VEGF injections about every 1-3 months, but eventually developed a blind painful eye from neovascular glaucoma. Histopathologic evaluation of the enucleated globe showed a peculiar difference of the tumor according to its topography, with features reminiscent of pilocytic astrocytoma at the optic nerve head and features reminiscent of subependymal giant cell astrocytoma at the retrolaminar optic nerve. We hypothesize that these changes occurred as a secondary effect of the anti-VEGF treatment. Conclusions . Anti-VEGF agents may decrease the ophthalmologic complications of RAH. We recommend that this treatment should be started early and continued for a protracted time at regular and frequent intervals. Moreover, a combination of therapies might prove to be superior to monotherapy and should therefore be considered in aggressive retinal astrocytic hamartomas.